Articulations between complex thinking and postmodern thinking - Arce Rojas, Rodrigo (2021)
This article aims to clarify the relationships between complex thinking and postmodern thinking. It also seeks to identify convergences and differences in order to establish possible synergies. It is concluded that although complex thinking is somehow heir to postmodernism, and some of its promoters and practitioners do not recognize such characterization, complex thinking has its own characteristics that make its representation more defined than postmodern thinking conceived as a mixture of trends and proposals. Since both dimensions do not have the same epistemological pretensions, it is not necessarily possible to speak of establishing bridges because there would be no interlocutors from postmodern thinking that could rather be typified as a cultural expression with different manifestations without clear recognition of time, spaces or characters. This situation does not happen with complex thinking that now has an initial but growing community of practitioners, scholars or promoters. This comparative exercise is useful to recognize the nature of complex thinking and its common ground with postmodern thinking.